‘Bhagwa’ Pomegranate Nectar: An Experimental Study - Bhatt, A. H.; Arbat, S. S.; Raj , Dev; Sitapara, H. H.; Shah , N. I. (Research Highlights in Agricultural Sciences Vol. 4, 2022)
The experiment of standardisation of different combinations of juice levels was used for pomegranate nectar preparation and evaluated for changes in biochemical, sensory, and quality parameters over a six-month storage period at room temperature. The experiment was conducted in the year 2013 to 2014 at the Department of Post Harvest Technology, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari. The increasing trend in TSS (17 to 17.51\(^{°}\) brix), reducing sugars (4.24 to 7.64 %) and total sugars (16.37 to 16.67 %) whereas decreasing trend in titratable acidity (0.35 to 0.30 %) and ascorbic acid (3.13 to 1.80 mg/100ml) was noticed irrespective of treatments during storage. Throughout the storage period, there was a decrease in the sensory parameters of nectar in terms of colour (8.34 to 7.78), flavour (8.72 to 8.09), and overall acceptability (8.56 to 7.94). There was no sedimentation and no colony (microbial growth) observed during Total Plate Count (TPC) in the pomegranate nectar during storage period.